Surgical Extent of Central Lymph Node Dissection for Papillary Thyroid Carcinoma Located in the Isthmus: A Propensity Scoring Matched Study - Shuai, Yanjie; Yue, Kai; Duan, Yuansheng; Zhou, Mengqian; Fang, Yan; Liu, Jin; Liu, Dandan; Jing, Chao; Wu, Yansheng; Wang, Xudong (Frontiers in Endocrinology, 2021)
Introduction: To assess the risk factor for the central lymph node (CLN) metastasis and investigated the surgery extent of lymph node dissection for patients with isthmic PTC (papillary thyroid carcinoma). Materials and Methods: A total of 669 patients with a single nodule of isthmic PTC were retrospectively reviewed. The propensity score matching was performed twice separately. 176 patients respectively from patients who underwent thyroidectomy plus bilateral central lymph node dissection (BCLND) and who underwent thyroidectomy plus unilateral central lymph node dissection (UCLND) were matched. 77 patients were respectively selected from patients who underwent thyroidectomy plus BCLND and who underwent thyroidectomy with no central lymph node dissection (NCLND) were matched. Results: Among all the patients who underwent BCLND, 81/177 (45.76%) was confirmed with histologically positive CLN metastasis, and the occult lymph node metastasis is 25.42%. The 5-year recurrence-free survival (RFS) rates were 92.9% in the NCLND group and 100% in the BCLND group with P<0.05, while there was no statistical difference in 5-year RFS between the BCLND group and UCLND group (P=0.11). The multivariate logistic regression analysis identified that age<55, tumor size>1cm, capsule invasion and lymphovascular invasion were significantly associated with CLN metastasis, while only age and lymphovascular invasion were proved to be independent risk factors related to contralateral CLN metastasis. Conclusions: The thyroidectomy with NCLND could be insufficient for patients with isthmic PTC especially for those patients with high risk of central lymph node metastasis, considering that the rate of occult lymph node metastasis could not be ignored.